CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IMPLEMENTATION OF CUSTOMER SATISFACTION AND LOYALITY IN PT. INDONESIA PORT CORPORATION TERMINAL PETIKEMAS (PT. IPC TPK) SUMBAGSEL - Adi Saputra Darmansyah; Diah Isnaini Asiati; Omar Hendro (STIE DWI SAKTI BATURAJA, 2020)
This study is entitled Implementation of Customer Relationship Management (CRM) Against Customer Satisfaction and Loyalty at PT. Indonesia Port Corporation Container Terminal (PT. IPC TPK) in SUMBAGSEL. This research method uses descriptive and inferential statistical analysis, with the path analysis model. The results of the study answer the problem formulation which is also the purpose of this study. First, the customer / focusing on key customers has a significant effect on Customer loyalty. Second, customer / focusing on key customers has a significant effect on Customer Satisfaction. Third, Organizing around CRM has a significant effect on Customer Satisfaction. Fourth, Organizing around CRM has a significant effect on Customer loyalty. Fifth, Managing knowledge has a significant effect on Customer Satisfaction. Sixth, Managing knowledge has a significant effect on Customer loyalty. Seventh, incorporating CRM-based technology has a significant effect on Customer Satisfaction. Eighth, incorporating CRM-based technology has a significant effect on Customer loyalty. Ninth, Customer Satisfaction has a significant effect on PT. Indonesia Port Corporation Container Terminal (PT. IPC TPK) Sumbagsel. Through the path analysis it is concluded that the path for the four independent variables and the two more effective dependent variables is the direct influence pathway, this can be seen from all the values ​​of the direct pathway value is higher if compared to the path of indirect influence. Researchers provide recommendations, first carry out new investments to replace equipment facilities that are old and often suffer damage according to customer needs. Second, make service service agreement (SLA) contract agreements and commit according to customer wishes. Third, make communication via social media be it Whatsapp, Facebook and so on as the customer wishes. Fourth, provide special training for officers who deal directly with CRM activities.